Isolation and characterization of oral Actinomyces strain from patients with periodontal disease - Eshraghi S.; Salari MH; Kadkhoda Z.; Yaghmaei Sh (Tehran University of Medical Sciences, 2001)
"nAbstract: Actinomyces species are normal residents of the mouth cavity, gastrointestinal tract and female genital tract. The genus consists of gram-positive bacteria, strictly anaerobic or microaerophilic. The bacteria are opportunists with a low virulence potential that cause actinomycosis only when the normal mucosal barriers are disrupted. The main purpose of this study was the isolation of Actinomyces strains and determining of their role in periodontal diseases. The present study was carried out on 100 patients with periodontal diseases referred to the Periodontic Department of Faculty of Dentistry. The sampling was done in 6 months with isolation of oral Actinomyces from microbial plaque and periodontal pocket. The samples were selected based on the following criteria: periodontal plaque with deep pocket (>3 mm), no antibiotic therapy for a period of at least two weeks, and lack of systemic diseases. One strain of Actinomyces viscosus and two strains of Actinomyces naeslundii were isolated from the patients with gingivitis and periodontitis. Of the 100 patients with gingivitis and periodontitis, aged between 18-57 years old, 46% were males and 54% were females. The peak incidence of the diseases (35%) was in the third age group (31-40) and the lowest incidence (10%) was in the first age group (<20). Forty patients (40%) complained of gingival disease and its bleeding with lower incidence of (42.5%) in female.